EMOTIONAL DISTRESS EXPERIENCED BY NURSING PROFESSIONALS IN A HEALTH CRISIS SITUATION - Monteiro, Wagner Ferreira; Ximenes, Vitória Miranda; Silva, Denise Maria Guerreiro Vieira da; Andrade, Lucas Lorran Costa de; Lima, Kássia Janara Veras; Ferreira, Darlisom Sousa; Ramos, Flávia Regina Souza (Cogitare Enfermagem, 2024)
Objective: to investigate the emotional repercussions experienced by nursing professionals during the COVID-19 pandemic in Manaus. Method: qualitative descriptive study. Data collection took place from June 2020 to February 2021, in the Amazonas state capital, Brazil, through semi-structured interviews with nursing professionals who worked on the front line, coded with the aid of the ATLAS.ti 8.0 program and analyzed according to the precepts of Thematic Network Analysis. Results: the 19 participants were nurses (68%) and nursing technicians/assistants (32%). Four themes emerged from the Emotional Impacts Thematic Network: unexpected changes, increased tensions, emotional distress, and psychosocial support strategies. Conclusion: the professionals' experiences should be used as a basis for initiatives to promote and protect their health, as well as their working conditions, in order to guarantee the quality of the care they provide.